Modeling the dispersal of the cryptogenic alga Chondria tumulosa (Rhodophyta, Ceramiales) in the Papahānaumokuākea Marine National Monument - James T. Fumo; Brian S. Powell; Randall K. Kosaki; Alison R. Sherwood (Aquatic Invasions)
The cryptogenic nuisance alga Chondria tumulosa was first observed in 2016 at Manawai (Pearl and Hermes Atoll) in the Papahānaumokuākea Marine National Monument. It has since spread across the atoll, growing in thick mats and smothering benthic habitat. In September 2021 the species was observed at Kuaihelani (Midway Atoll), ~130 km to the northwest. Due to its growth habit and recent spread, considerable concern has been raised and management of the species may be warranted. We used publicly available oceanographic data and the Connectivity Modeling System software to assess how the potential for successful dispersal of C. tumulosa is affected by particle properties and oceanographic conditions. We found the likelihood of successful transit to be linked to particle density, oceanographic conditions at the time of release, and release location. Further modeling explicitly targeted the capacity of both reproductive tetraspores as well as drifting fragments to disperse. Model results indicated tetraspores of C. tumulosa are unlikely to survive the transit from Manawai to Kuaihelani, as none arrived at Kuaihelani above the depth limit of the species and those arriving below successfully settled at a rate of only 0.02%. In contrast, fragments modeled as rafting on marine flotsam such as macroalgae and marine debris settled at a rate of 3.85%. Rafting fragments also settled ~600 km further to the southeast (towards the Main Hawaiian Islands) than tetraspores. This study identified oceanographic conditions and particle properties likely to aid dispersal of C. tumulosa to Kuaihelani and suggests that fragments rafting on marine flotsam may accelerate its spread.